The Effects of Interest Rate Changes on Stock Prices of Banks in China - Xu, Shijia (2011)
This paper presents the interest rate effects on the banking stock prices in China. It focuses on the announcement dates to measure the effects of interest rate changes on the bank stock returns. The study chooses four interest rate increases and four decreases during 2002-2010. The study finds that there is normally a negative relationship between interest rate changes and stock returns. When interest rate increases, stock prices decreases, and when the interest rate decreases, the stock prices increases in China.